Reduplication revisited: verbal plurality and exhaustivity in the visual-gestural modality - Quer, Josep (Sensos-e, 2019)
From the very early stages of sign language research (Klima & Bellugi, 1979 for ASL) and in subsequent descriptions of unrelated sign languages, a reduplicative morpheme in verbal morphology has been identified as encoding exhaustive distribution over a plural argument in agreement verbs. It consists in a sideward reduplication of the verb sign on the horizontal plane, where the repeated endpoints match the referential locus of a plural argument. It is often labelled as [+distributive/exhaustive] and considered a mark of plural argument agreement. However, in Klima & Bellugi (1979, p. 284) it was called “distributional aspect”, highlighting the link to inflectional aspectual properties. On the basis of Catalan Sign Language (LSC) data, this paper reconsiders the status of the alleged [+distributive/exhaustive] morpheme under the light of verbal plurality marking and argues for a broader analysis of reduplication in the verbal domain built on the category of pluractionality, in line with Kuhn & Aristodemo (2017). This change in vantage point allows for a better understanding of reduplication in sign languages as a grammatical marker of plurality cutting across the parameters of event participants, event times and event locations. Artigo Completo